Biodegradation of chlorobenzene and chlorophenols by pseudomonas cultures - Bhaskar, Gaikwad G.; Rita, Varma J. (Research Journal of Chemistry and Environment, 2013)
Cultures from NCIM culture collection (National Chemical Laboratory, Pune, India) were screened for biodegradation chlorobenzene (CB). A strain, Pseudomonas sp. NCIM 2303, was found to be most effective. The biodegradation was carried out in aqueous solution by resting cells. The decomposition of 0.02% CB was 96.64% in 24h. We have screened cultures for biodegradation of o-chlorophenol and p-chlorophenol. Pseudomonas sp. NCIM 2668 has shown 94.59% degradation of 0.15% o-chlorophenol. Pseudomonas sp. NCIM 2668 has shown 31.42% degradation of 0.2% p-chlorophenol.
Keywords: Biodegradation; chloride; chlorobenzene; etc.; pollution; Pseudomonas sp